2020
DOI: 10.5688/ajpe7586
|View full text |Cite
|
Sign up to set email alerts
|

Global Health Learning Outcomes in Pharmacy Students Completing International Advanced Pharmacy Practice Experiences

Abstract: Objective. To examine the global health learning outcomes of Doctor of Pharmacy (PharmD) students from three US schools who participated in international advanced pharmacy practice experiences (APPEs). Methods. A mixed-methods, prospective study was used to assess fourth-year PharmD students at three US pharmacy schools who participated in an international APPE during the 2017-2018 academic year and a matched cohort (control group) of PharmD students who did not participate in an international APPE. To evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
1
15
0
1
Order By: Relevance
“…While the objective of two prior studies of this research was to determine what students learned while abroad on international APPEs, discussion with the research team and analysis of the analytic memos from the coding process revealed new questions as to how students learned these outcomes while abroad [14,15]. Utilizing the aforementioned codebook (Supplementary Materials), the researchers went back to the original open response survey and focus group data and analyzed these through the lens of Mezirow's Transformative Learning Theory and Kolb's Experiential Learning Theory to examine the connectivity between codes as students progressed on their international APPE [8,9].…”
Section: Study Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the objective of two prior studies of this research was to determine what students learned while abroad on international APPEs, discussion with the research team and analysis of the analytic memos from the coding process revealed new questions as to how students learned these outcomes while abroad [14,15]. Utilizing the aforementioned codebook (Supplementary Materials), the researchers went back to the original open response survey and focus group data and analyzed these through the lens of Mezirow's Transformative Learning Theory and Kolb's Experiential Learning Theory to examine the connectivity between codes as students progressed on their international APPE [8,9].…”
Section: Study Methodsmentioning
confidence: 99%
“…Further, there is no research on how the learning outcomes from these core competencies may interact with each other to explain how students actually learn while abroad. From 2017-2018, researchers from three Universities assessed knowledge, skills, and attitudes of student pharmacists who completed international APPEs using the CUGH global competency framework [14,15]. The purpose of this study is to describe the development of a new learning model that helps describe how student pharmacists acquired their learning outcomes during an international APPE.…”
Section: Introductionmentioning
confidence: 99%
“…A more parsimonious model was derived using backward selection with a criteria of p,.10, which is the default criteria for retaining predictors during backward selection in many statistical packages. 20,21 In other words, the parsimonious model was generated iteratively by removing variables with the highest p values in a stepwise fashion until all variables in the model were p,.10. Parsimonious models explain the data with a minimum number of predictor variables.…”
Section: Methodsmentioning
confidence: 99%
“…These experiences increase student pharmacists' cultural awareness, selfawareness, and knowledge of public health, while providing an environment for them to gain confidence in providing clinical care and making recommendations. [39][40][41] For students interested in a career with a public health emphasis, engaging in domestic and international outreach events is a way to gain a deeper appreciation for disparities in health.…”
Section: Unique Opportunities For Students In Ambulatory Carementioning
confidence: 99%